2003
DOI: 10.1046/j.1439-0426.2003.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublethal concentrations of copper on the growth performance of Oreochromis niloticus

Abstract: The study evaluated the effect of different sublethal concentrations of copper in water (0, 0.15, 0.3 and 0.5 p.p.m.) on the behavioural response, growth performance, and whole body and liver composition of Oreochromis niloticus. Hyperactivity and reduced exploratory behaviour were observed when fishes were subjected to different levels of copper in water as compared with the control. Fish refused to accept the feed immediately after exposure and only began taking it up after about 4-5 h as compared with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…Ali et al (2003) observed reduced growth of Oreochromis niloticus under different (0, 0.5, 0.3, & 0.5 ppm) water-borne Cu levels (Ali et al 2003). Also these results are in accordance with the findings of Mohanty et al (2009) that determined the effect of copper on survival, growth and feed intake of Indian major carp, C mrigala for 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (2003) observed reduced growth of Oreochromis niloticus under different (0, 0.5, 0.3, & 0.5 ppm) water-borne Cu levels (Ali et al 2003). Also these results are in accordance with the findings of Mohanty et al (2009) that determined the effect of copper on survival, growth and feed intake of Indian major carp, C mrigala for 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…This has already been shown in a number of aquatic animals exposed to copper, which is known to affect a range of endpoints such as oxygen consumption, blood variables, and energy efficiency (US EPA, 2003), with possible consequences on individual performances. Such effects have been extensively investigated in fish (DeBoeck et al, 1997a, b;Handy et al, 1999;Smith et al, 2001;Campbell et al, 2002;Ali et al, 2003), amphibians (Mounaji et al, 2003;Carattino et al, 2004;Redick and La Point, 2004), and molluscs (Widdows and Johnson, 1988;Belanger et al, 1990;Cheung and Wong, 1998;Elfwing and Tedengren, 2002). Effects of copper on the energetic costs associated with individual performances have also been studied in arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…Swift and simplified information allied to the advantages gained by the fish is conveyed by condition factor which seizes immense connotation, for the reason that diminution in condition factor causes hypoxia that entails negative effect on the feed intake of fish, moreover lessens Table 2 Mean values of physico-chemistry variables determined during growth trails for treated and control fish species condition factor and growth also (Randall and Yang, 2004). Ali et al (2003) observed significant variations in specific growth rate and condition factor and weight gains of Oreochromis niloticus grown under different sub-lethal concentration of water-borne Cu. Dethloff et al (2001) found no significant difference in condition factor values of rainbow trout collected from different sites polluted with Cr, Cd and Se.…”
Section: Discussionmentioning
confidence: 90%